INFLUENCE DEEP EDUTAINMENT METHOD INCREASE RESULTS STUDENT LEARNING AT SCHOOL - Hishnudin, As'ad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
As for This research was carried out on the day Monday 25 December 2023. This research is in background back problem results Students' learning is increasing day decreases, so can decreasing values. Learning is carried out by teachers, because that's what teachers have to do correct results Students study with good and correct grades. assessing students means the same as assessing How method the teacher teaches , the students also get it . Can it is also known that method learning influence results Student learning at school, possible in every learning must use productive method , failure a Student not only is in the value results Study but it also lies in the teacher's internal skills field learning . So do some the method being practiced when learning taking place like method Expository only emphasizes understanding course, so allows students to feel fed up because monotonous teacher teaching Then researcher choose method Edutainment in field this learning , because very help existing problems in the classroom . This research contains 5 roles. First peneti as subject, both Students as object in field , the three teachers as data source Analysis of results study, the four schools as place study . Fifth method study as tools used for interviews.